2022
DOI: 10.3390/ijms232012071
|View full text |Cite
|
Sign up to set email alerts
|

Design of Cyclic Peptide-Based Nanospheres and the Delivery of siRNA

Abstract: In recent years, cyclic peptides have attracted much attention due to their chemical and enzymatic stability, low toxicity, and easy modification. In general, the self-assembled nanostructures of cyclic peptides tend to form nanotubes in a cyclic stacking manner through hydrogen bonding. However, studies exploring other assembly strategies are scarce. In this context, we proposed a new assembly strategy based on cyclic peptides with covalent self-assembly. Here, cyclic peptide-(DPDPDP) was rationally designed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…In recent years, many different materials such as nanofibers [1,2], nanotubes [3,4], nanospheres [5,6],and hydrogels (HGs) [7,8] have attracted increasing interest as suitable and innovative platforms for biomedical and pharmaceutical applications [9][10][11], including tissue engineering [12,13] and the delivery of drugs [14,15] or diagnostic agents [16,17]. Hydrogels are three-dimensional macroscopic networks able to retain large amounts of water or other biological fluids [18].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many different materials such as nanofibers [1,2], nanotubes [3,4], nanospheres [5,6],and hydrogels (HGs) [7,8] have attracted increasing interest as suitable and innovative platforms for biomedical and pharmaceutical applications [9][10][11], including tissue engineering [12,13] and the delivery of drugs [14,15] or diagnostic agents [16,17]. Hydrogels are three-dimensional macroscopic networks able to retain large amounts of water or other biological fluids [18].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the flow apoptosis assay showed that MnO 2 @BSA‐Cy5.5 induced apoptosis rates of 8.56% and 7.21% in Nthy‐ori3‐1 and 8305C cells, respectively, which were not significantly different from the PBS‐treated groups (Figure 4C). As shown in (Figure 4B), the hemolysis rate was only 3.23% in the highest concentration of 200 μg/mL of MnO 2 @BSA‐Cy5.5, which was lower than the 5% that could induce hemolytic effect 18 . Cytotoxicity and hemolysis assays showed that our prepared MnO 2 @BSA‐Cy5.5 have good biosafety and can be further used for in vivo studies.…”
Section: Resultsmentioning
confidence: 84%
“…As shown in (Figure 4B), the hemolysis rate was only 3.23% in the highest concentration of 200 μg/mL of MnO 2 @BSA-Cy5.5, which was lower than the 5% that could induce hemolytic effect. 18 Cytotoxicity and hemolysis assays showed that our prepared MnO 2 @BSA-Cy5.5 have good biosafety and can be further used for in vivo studies.…”
Section: Cytotoxicity and Hemolysis Assaymentioning
confidence: 89%
“…35 While this system is restricted to small-length peptides, the resulting scaffold shares the characteristic tunability of LPCs via amino acid substitutions, as evidenced by changes in molar uptake of Nile red in response to substitutions at the pore-facing residues. 35 Similarly, cyclic peptide nanotubes (cPNTs) have received increasing attention in recent years for a number of applications, particularly for therapeutic delivery, 36,37 owing to their high biocompatibility and ease of synthesis. Similar to LPCs, cPNTs can be synthesized with a range of pore sizes, 38,39 in some cases as high as 2 μm in diameter.…”
Section: Synthesis Methodsmentioning
confidence: 99%